Techno-economic comparison between CSP plants presenting two different heat transfer fluids. (15th April 2016) - Sau, S.; Corsaro, N.; Crescenzi, T.; D'Ottavi, C.; Liberatore, R.; Licoccia, S.; Russo, V.; Tarquini, P.; Tizzoni, A.C.
Highlights: CSP parabolic trough technology: comparison between two systems using different HTFs. Thermo-physical characterization and comparison between two HTF binary mixtures. Thermal stability analysis and comparison between the above mentioned HTFs. Solar parabolic plant components sizing considering the two mentioned configurations. Techno-economic analysis according to the estimated electric energy cost per KW h. Abstract: The employment of parabolic trough solar power plants (PT-CSP) for electrical power and process heat generation is one of the most promising technologies for carbon free energy production. The selection of thermal fluids, both for the heat transfer (heat transfer fluid, HTF) and the storage (heat storage material, HSM), is a crucial point for increasing CSP efficiency and cost effectiveness. In this paper two different PT-CSP configurations, both presenting a double tanks storage system, are compared. In particular, two different medium size (50 MWe) plant schemes, presenting two different working fluids as HTF, are described and analysed. In the first scheme a "binary" molten salt mixture, composed of sodium and potassium nitrate, is considered, while, in the second one, the employment, as HTF, of a "ternary" mixture, consisting of sodium potassium and lithium nitrates, is investigated. In both cases, the binary mixture is used for thermal storage (HSM). The first scheme represents the configuration developed by ENEA and already used for the Archimede plant in Priolo Gargallo (Sicily-Italy). The second one is an innovative proposal, which aims to improve CSP plants performances and to reduce operating costs. In particular, since the ternary mixture has a considerably lower freezing temperature than the binary one, this solution allows to keep the system at a lower temperature overnight, so reducing thermal energy losses. In first instance, it is necessary to characterize the binary and ternary mixtures respect to their thermo-physical features. The two CSP configurations are then sized and, by a techno/economic evaluation, compared with respect to the calculated unit cost of electricity production.